2013
DOI: 10.1093/restud/rdt017
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Group Formation via Unproductive Costs

Abstract: Sacrifice is widely believed to enhance cooperation in churches, communes, gangs, clans, military units, and many other groups. We find that sacrifice can also work in the lab, apart from special ideologies, identities, or interactions. Our subjects play a modified VCM game—one in which they can voluntarily join groups that provide reduced rates of return on private investment. This leads to both endogenous sorting (because free-riders tend to reject the reduced-rate option) and substitution (because reduced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 61 publications
(63 reference statements)
3
34
0
Order By: Relevance
“…However, this limit case again triggers similar dynamics towards the other group, leading to a cyclical pattern: There is permanent change in social structure with high types starting out to separate from the 4 lannaccone (1992) looks at a comparable mechanism to explain seemingly unproductive behavior in the context of religion and cults. Aimone et al (2013) also provide experimental evidence. However, in these papers, screening out low types provides an additional benefit to in-group members as it also affects the relative costs of carrying out the costly action.…”
mentioning
confidence: 85%
“…However, this limit case again triggers similar dynamics towards the other group, leading to a cyclical pattern: There is permanent change in social structure with high types starting out to separate from the 4 lannaccone (1992) looks at a comparable mechanism to explain seemingly unproductive behavior in the context of religion and cults. Aimone et al (2013) also provide experimental evidence. However, in these papers, screening out low types provides an additional benefit to in-group members as it also affects the relative costs of carrying out the costly action.…”
mentioning
confidence: 85%
“…5 Precise answers on the questions we address are di¢ cult to extract from these data for a number of reasons. First, each international con ‡ict has a number of idiosyncratic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Page et al (2005) showed that the endogenous group formation is helpful in sustaining cooperation, compared with the control treatment without such endogenous 14 Also see Aimone et al (2013).…”
Section: Hypothesis 3(e): the Percentage Of Subjects That Sort Into Tmentioning
confidence: 99%